Prevalência e fatores associados à ansiedade em estudantes de medicina da Universidade Federal do Amapá - (:unkn) unknown (UNIFAP – Universidade Federal do Amapá, 2017)
Medical school provides a stressful environment that can trigger anxiety disorder. This study aims to accesses the prevalence and factors associated with anxiety symptoms in medical students of a Brazilian university. It was performed a cross-sectional, observational and quantitative study conducted with 195 undergraduate medical students from the first to sixth grade of the course. Therefore, it was used the State-Trait Anxiety Inventory (STAI), the Dundee Ready Education Environment Measurement (DREEM) and a sociodemographic questionnaire. Data analysis was performed with the chi-square test and differences were considered significant when p<0,05. As results, 59.8% (n = 116) of the students were classified with moderate-to-severe anxiety (symptomatic anxiety) through the IDATE-E and 61.53% (n = 120) by the IDATE-T. Furthermore, the variables associated with the occurrence of trait-anxiety were gender, age, marital status, depression, social relationship, willingness to change course and perception of the teaching environment. Factors associated with state-anxiety were gender, locomotion, physical activity, depression, social relationship, reason to study medicine, leisure activity, willingness to change course and teaching environment. Taken together, these findings suggest that the prevalence of anxiety in medical students is higher than that found in the general population.
Keywords: Estudantes de medicina; Ansiedade - Estudantes; Estudantes de medicina - Saúde mental; Estudantes de medicina - UNIFAP; CNPQ::CIENCIAS DA SAUDE::MEDICINA